An Effective and Safe Laser Treatment Strategy of Fractional Carbon Dioxide Laser for Chinese Populations with Periorbital Wrinkles: A Randomized Split-Face Trial - Xianglei Wu; Qingqing Cen; Jian Jin; Wei Gao; Ying Shang; Linting Huang; Xiaoxi Lin (Dermatology and Therapy)
Abstract Introduction Ablative carbon dioxide fractional laser (CO2 AFL) can alleviate static wrinkles; however, its use in East Asian populations can predispose them to postinflammatory hyperpigmentation (PIH). We aimed to explore the optimum energy and coverage parameters of CO2 AFL for treating static periorbital wrinkles in a Chinese population and to minimize PIH incidence. Methods In total, 30 patients with static periorbital wrinkles were recruited. The PIH intervention side (1% hydroquinone cream every night on one periorbital area for each patient 1 month before and from the 8th day to 1 month after each treatment) and group (group A: 15‒20 mJ, 5%; group B: 10‒12.5 mJ, 15%; and group C: 12.5‒15 mJ, 10%) were determined randomly. The patients underwent two sessions of CO2 AFL at 3-month intervals. Follow-ups were conducted until 6 months after the last treatment. Results Overall, 20 participants (48.1 ± 13.1 years) completed all follow-ups without any serious complications. The application of hydroquinone significantly reduced PIH (p = 0.02). Both the investigators’ and patients’ visual evaluations demonstrated a consistent efficacy rate of 68.2% without differences between groups. The Fitzpatrick wrinkle score significantly decreased compared with pre-treatment (p < 0.01); however, a significant reduction only in group B at 3 months (p = 0.016) and 6 months (p = 0.001) post-treatment was observed. Groups B and C demonstrated significant reductions in superficial and deep wrinkles and pigmentation (p < 0.01). Conclusions CO2 AFL effectively reduced static periorbital wrinkles in the Chinese population. Low energy combined with high-density coverage was the most efficacious. The application of hydroquinone significantly reduced PIH incidence. Trial Registration Chinese Clinical Trial Registration no. ChiCTR2400087320 (date of trial registration: 25 July 2024).